SWOT-Analytic Hierarchy Process (AHP) of Agriclinics and Agribusiness Center (ACABC) Scheme - AFROZ, SHAFI; SINGH, RASHMI; NAIN, M S; MISHRA, J R; KUMAR, PRAMOD; KHAN, S A; IQUEBAL, M A (The Indian Journal of Agricultural Sciences, 2021)
Agriclinics and Agribusiness Center (ACABC) scheme was launched by the Government of India in 2003 as a strategy for boosting agribusiness in the country through agriculture graduates. Since its inception, a substantial number of agribusiness of different kinds started in the country, and hence expanded the agribusiness environment in the country, employed a vast population, and stretched extension services to the needy farmers even in remote villages. Therefore, it was essential to understand the panoramas of the scheme from its stakeholders. Hence the perception of the agripreneurs about the ACABC scheme was examined by measuring the strengths, weaknesses, opportunities, and threats quantitatively by combining SWOT with the analytical hierarchy process (AHP). A one-day interaction meet consisting of successful agripreneurs under the Nodal Training Institute (NTI)-Varanasi was held in Varanasi (UP), in October 2018 to administer the SWOT-AHP analysis. The results revealed that ACABC scheme had high positive (84.7%) features, and act as a suitable plan for promoting agribusinesses. The most significant positive features were the potentiality of employment generation under the scheme and the favourable attitude of self-employment among agriculture graduates. Delays in subsidy release under the scheme and less practical exposure of successful agribusiness to trainees under the scheme were the areas that need improvement which impedes the success of the scheme. The greater success of the scheme will enhance self-employment among agriculture graduates who will supplement the efforts of public extension by necessarily providing extension and other services to the farmers and, hence ACABC scheme can support the efforts of the Government for doubling the incomes of farmers.